2013
DOI: 10.1111/codi.12177
|View full text |Cite
|
Sign up to set email alerts
|

PROSPER: a randomised comparison of surgical treatments for rectal prolapse

Abstract: Aim Rectal prolapse is a profoundly disabling condition, occurring mainly in elderly and parous women. There is no accepted standard surgical treatment, with previous studies limited in methodological quality and size. PROSPER aimed to address these deficiencies by comparing the relative merits of different procedures.Method In a pragmatic, factorial (2 9 2) design trial, patients could be randomised between abdominal and perineal surgery (i), and suture vs resection rectopexy for those receiving an abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
184
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 17 publications
8
184
3
8
Order By: Relevance
“…One patient died (1.2%). Other studies have found higher mortality, and some have found lower (3,11). considering the fact that many patients were old, we believe that complication and mortality rates found in this study are acceptable.…”
Section: Discussionsupporting
confidence: 52%
“…One patient died (1.2%). Other studies have found higher mortality, and some have found lower (3,11). considering the fact that many patients were old, we believe that complication and mortality rates found in this study are acceptable.…”
Section: Discussionsupporting
confidence: 52%
“…Since that time, over 100 different surgical procedures have been proposed for the management of this condition [3,4]. Although the majority of these procedures are now of only historical interest, many different techniques are still being used today.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal operations seem to result in lower recurrence rates but there are no randomized controlled trials substantiating this. 5,6 Perineal procedures avoid laparotomy/laparoscopy, and therefore, may have a lower operative risk and morbidity. They may, therefore, be more suitable for older or high-risk patients with a relevant co-morbidity, although again there are no adequately powered RCTs to back these recommendations up.…”
Section: Operation Proceduresmentioning
confidence: 99%